Pengaruh Religiusitas dan Pengetahuan Produk Halal pada Minat Pembelian Produk E-commerce pada Mahasiswa UIN Jawa Timur - Moh Holilur Rohman; Lifia Lifia; Muhammad Haris Hidayatulloh (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Interest in buying in Indonesia is very important in the world of e-commerce every year increasing from 2017 there were 70.8 million to predictions for 2024 as many as 189.6 e-commerce users, this is not spared by students where the electronic world dominates, namely university students spread across Indonesia, 100% Islamic students are at UIN. The purpose of this study was to see halal labeling as mediation in buying interest in e-commerce products with religiosity and knowledge of halal products as variable Z by using the SmartPLS analysis tool. The results of this study show that the mediation aspect of halal labeling on religion has a full mediation effect, while halal labeling has a partial mediation effect on the interest in buying e-commerce products in UIN students in East Java. Meanwhile, religiosity has no effect on purchase intention with a t-statistic value of 1.430 <1.96 and a p-value of 0.153 > 0.05. on aspects of religiosity. Keywords: Religiosity, Knowledge of Halal Products, Purchase Intention.